MANFAAT MINDFULNESS TRAINING UNTUK MENGURANGI KECEMASAN PADA PASIEN KANKER DENGAN KEMOTERAPI - Jenita Doli Tine Donsu; Surantono Surantono; Kirnantoro Kirnantoro (Caring : Jurnal Keperawatan, 2017)
Anxiety can impair the ability of cancer patients to run chemotherapy. Mindfulness training with meditation methods can improve empathy for self in activating affective, cognitive, moral, intra and interpersonal dimension so as to decrease anxiety especially in cancer patient who will undergo chemotherapy. The purpose of this study was to determine the benefits of mindfulness training in reducing anxiety in cancer patients with chemotherapy. The research method used Quasi experiment design with pretest and posttest control group design, in 60 samples taken at Indonesia Cancer Foundation in Yogyakarta, analyzed with Mann Whitney z distribution test for category ordinal and t-test data for experiment and control group differences. The results showed most of the characteristics of age >40 years and female gender with breast cancer type. Conclusions were obtained, mindfulness training can provide benefits for cancer patients in achieving relaxation in order to reduce anxiety when faced with treatment with chemotherapy action, thereby raising awareness to better accept the situation conditions that are happening. Suggestions that health care workers both nurses and doctors can train patients who experience anxiety in the face of chemotherapy or other invasive measures.